Evidence of extreme habitat stability in a Southeast Asian biodiversity hotspot based on the evolutionary analysis of neotenic net-winged beetles - Malohlava, V; Bocak, L (Molecular ecology, 2010)
The diversification of neotenic beetle lineages has not been studied, despite the potential for defining biodiversity hotspots and elucidating the history of regional faunas. Additionally, neotenics may provide insight into the process of speciation in small populations with extremely low dispersal ability and a limited range. Here, we used two rDNA and three mtDNA markers to investigate the phylogeny of Scarelus, a neotenic lineage endemic to Southeast Asian rainforests. Most genetic differentiation was associated with Palaeogene geographical divisions, which remain distinct despite temporary connections. Dispersal events were rare, with only two inferred for Scarelus: from Borneo to the Philippines 28.3 million years ago (Ma) and from Sumatra to Java 13.9 Ma. We suggest that speciation resulted from allopatric range fragmentation, and Scarelus diversified readily when conditions were favourable; in this case, at different times in the eastern (19.3-39.1 Ma) and western (3.5-13.9 Ma) parts of Sundaland. The observed strong phenotypic similarity was preserved under speciation through complete allopatry. Neotenic Lycidae have survived for a long time in very stable habitats, and extremely low dispersal activity has not limited their persistence; however, the long-term diversification rate of neotenics is low and diversification is nonexistent under stable conditions. The modern ranges of neotenic lineages are indicative of ancient rainforest refugia and may be used in biodiversity conservation management. Most neotenics are at risk of extinction because of their small ranges and a low dispersal potential.
Keywords: zachování přírodních zdrojů; Animals; biodiverzita; ribozomální DNA; DNA, Ribosomal; Geography; Conservation of Natural Resources; Coleoptera; Genetic Speciation; DNA, Mitochondrial; brouci; jihovýchodní Asie; zeměpis; Phylogeny; Male; mitochondriální DNA; Biodiversity; Sequence Analysis, DNA; vznik druhů (genetika); ekosystém; Ecosystem; zvířata; mužské pohlaví; sekvenční analýza DNA; fylogeneze; Asia, Southeastern